Rheological and mechanical study of micro-nano sized biocarbon-PLA biodegradable biocomposites - Md. Rezaur, Rahman; Al-Khalid, Hj Othman; Yuriy, Yurkin; Andrey, Burko; Ulyana, Shestakova; Muhammad Khusairy, Bakri; Sulaiman Y., Alfaifi; O., Madkhal; Mahmood D., Aljabri; Mohammed M., Rahman (NC State University, 2023)
Pinewood sawdust was pyrolyzed to create a micro-nanocarbon. The adsorbent’s particle size was reduced during a ball milling procedure to improve the surface area and encourage porosity growth. The synergistic effects of micro-nano-adsorbent-reinforced poly(lactic acid) (PLA) composites were investigated by analyzing the efficiency of the rheological process. The properties of the prepared composites also were examined using various characterization tests, including tensile and hardness tests, crystallinity tests, elemental composition, and plasticity behavior tests. Therefore, in-depth investigations and comparisons were also carried out to confirm the created composites’ efficacy compared to other outcomes.